Building Blocks for Raising Healthy and Successful Youth: A Profile of Development Assets of Youth Living in Tirana City, Albania - Nano, Livia (Richtmann Publishing, 2012)
This paper begins by shortly presenting two approaches to helping young people grow up healthy and successfully: 1)problems’ prevention / reduction approach and 2) strength-based approach; by emphasizing the need to find a balance betweenthe two. Furthermore, the paper focuses on the strength-based approach by presenting Search Institute’s Development AssetFramework. This framework identifies 40 elements of young people’s positive growth and development. This section is followedby an overview of the state of development assets among young people attending public secondary and high schools of Tiranacity, in Albania, by providing an analysis according to eight assets categories (support, empowerment, boundaries andexpectations, constructive use of time, commitment to learning, positive values, social competencies and positive identity) aswell as according to five context areas (personal, family, school, social and community). The paper concludes by stressing thepower of development assets and the role that everyone may play in building these assets.